THE IMMEDIATE EFFECT OF THE AQUALIZER® HYDROSTATIC SPLINT ON THE MASTICATORY MUSCLES ACTIVITY AND POSTURAL BALANCE - Hantoiu, Liana Georgiana; Cerghizan, Diana; Popsor, Sorin (European Scientific Journal, ESJ, 2013)
The correlation between the body posture and dental occlusion is well known. The aim of this paper is to highlight the effect of the immediate application of a hydrostatic splint on the postural balance and masticatory muscles activity. Material and method: Fifteen subjects were included in this study and they were examined by means of surface electromyography and posturometric assessement. The Mann Whitney U test was applied to compare the obtained results before and after the insertion of the Aqualizer® splint. Results: No statistically significant differences in the electromyographic activity and the postural balance after the immediate insertion of the hydrostatic splint could be observed ( p > 0.05).Conclusions: In the limits of the present study, there are no significant differences in the masticatory muscles electromyographic activity and in the postural balance immediate after the insertion of Aqualizer® splint. Further investigations concerning the immediate effect of the Aqualizer® splint on healthy as well as dysfunctional subjects have to be carried out.